GURU SEBAGAI PILAR UTAMA PEMBENTUKAN KARAKTER - Wahab, Jamal (Inspiratif Pendidikan, 2022)
The teacher is a role model, both in terms of knowledge and personality for his students. The role of the teacher is contained in article 3 of Law no. 20 of 2003 concerning the National Education System, which states that national education functions to develop capabilities and form dignified national character and civilization in the context of educating the nation’s life, aims to develop the potential of students to become human beings who believe and fear God Almighty, have good morals noble, healthy, knowledgeable, capable, creative, independent, and a democratic and responsible citizen. Character in Greek and Latin, character comes from the word charassein which means to carve a permanent and indelible pattern. Character or character is a combination of all human traits that are permanent so that it becomes a special sign to distinguish one person from another. Individuals with good character are individuals who can make decisions and are ready to take responsibility for any consequences of the decisions they make. three stages of character formation, namely: Moral knowing, namely understanding well in children about the meaning of goodness. Moral feeling, namely building a love of good behavior in children which will become a source of energy for children to behave well. Moral feeling is strengthening the emotional aspects of students to become human beings with character. This reinforcement is related to the forms of attitude that must be felt by students, namely awareness of identity, self-confidence, sensitivity to the suffering of others, love of truth, self-control, and humility. Moral action is how to make moral knowledge into real action.